Теоретичні положення імплементації цілей сталого розвитку в стратегічне управління підприємством - Манойленко, Олександр Володимирович; Гао, Лян (Національна академія управління, 2024)
В сучасних умовах господарювання для підприємств актуалізується потреба досягнення довгострокової конкурентоспроможності, підтримка якої можлива на основі інтеграції цілей сталого розвитку (ЦСР) у процеси ціннісно-орієнтованого стратегічного управління. Об’єктивізація потреби балансування економічних показників з екологічною та соціальною відповідальністю доводить необхідність розбудови теоретичного підґрунтя такої інтеграції. Метою дослідження постав розвиток теоретичних положень та методичних рекомендацій щодо імплементації цілей сталого розвитку в стратегічне управління процесами створення цінності підприємства. Досягнення заданої мети базується на гіпотезі щодо існування прямого зв'язку між рівнем імплементації ЦСР та вартістю підприємства, проявом якої є позитивний вплив на неекономічні (репутація та ESG-рейтинги) та економічні (прибутковість та ринкову капіталізацію) характеристики. Розроблений теоретичний базис складається з дванадцяти взаємопов'язаних положень, згрупованих на п'яти ієрархічних рівнях: концептуальному, оціночному, інструментальному, стратегічному та операційному. Центральним елементом концепції є визнання дихотомічної природи цінності в контексті сталого розвитку та прийняття зонтичної концепції щодо корпоративної соціальної відповідальності та ESG-практик. Новизна роботи полягає у структурованому підході до імплементації ЦСР з конкретними методами, принципами та очікуваними результатами для кожного теоретичного положення; в типологізації стратегічної поведінки на основі аналізу розриву між рівнем імплементації ЦСР на підприємстві та галузевими практиками; введенні поняття екосистеми ЦСР та прийнятті збалансованого портфельного підходу до проектів соціальної відповідальності в економічному, екологічному та соціальному вимірах. Практичну цінність мають рекомендації щодо систематизації зон уваги керівників соціально-відповідальних проектів, до яких віднесено індикатори для моніторингу та потенційні бар'єри реалізації кожного з введених положень. Формалізація таких зон уваги є основою для відстеження ходу імплементації ЦСР, коригування стратегії створення цінності відповідно до виявлених перешкод за для створення довгострокових конкурентних переваг.

The critical need for enterprises to shift from short-term financial goals toward long-term competitiveness explains the necessity to integrate Sustainable Development Goals (SDGs) into strategic management processes. As businesses face increasing pressure to balance economic performance with environmental and social responsibilities, developing theoretical frameworks for such integration has become essential for creating new management paradigms that effectivelynal changes while ensuring sustainable business development. The research aims to develop theoretical principles and methodological recommendations for implementing SDGs into strategic value-creation processes at the enterprise level. The study advances the hypothesis that a direct relationship exists between the level of SDG implementation and enterprise value, manifested through positive impacts on non-economic components (ESG ratings) and economic indicators (profitability and market capitalization). A comprehensive theoretical framework comprises twelve interconnected statements organized across five hierarchical levels: conceptual, evaluative, instrumental, strategic, and operational. The framework's central element recognizes the dichotomous nature of value in sustainable development contexts, encompassing both economic and non-economic components. Building on this foundation, the research establishes sustainable development as an umbrella concept relative to corporate social responsibility and ESG management practices, guiding the transformation of value-creation processes. The paper's novelty is demonstrated through its structured approach to SDG implementation with specific methods, principles, and expected outcomes for each theoretical position. Particularly innovative is the development of a strategic behavior typology (moderate, adaptive-moderate, adaptive-active, and active) based on analyzing the gap between an enterprise's SDG implementation level and industry practices. The research further introduces the concept of an "SDG ecosystem" and a balanced portfolio approach to social responsibility projects across economic, environmental, and social dimensions. The study contributes practical guidance through a detailed table of project manager attention zones, including measurement indicators and potential implementation barriers for each theoretical position. This framework enables enterprises to monitor implementation progress, identify obstacles, and adjust strategies accordingly, ultimately enhancing reputation, competitive advantages, and stake holder trust while creating sustainable long-term value.
Theoretical framework for integrating sustainable development goals into enterprise strategic management
Keywords: стратегічне управління; цілі сталого розвитку; створення цінності; теоретичний базис; strategic management; sustainable development goals; value creation; theoretical framework